The Broader Impact of Friend to Friend (F2F): Effects on Teacher–Student Relationships, Prosocial Behaviors, and Relationally and Physically Aggressive Behaviors. (July 2016) - Leff, Stephen S.; Waasdorp, Tracy Evian; Paskewich, Brooke S.
Girls often harm others' social standing by starting rumors about peers or by excluding others from peer group activities, which is called relational aggression. Although relational aggression is not a new phenomenon, there have been relatively few interventions designed to address this, especially for urban ethnic minority girls. The Friend to Friend (F2F) program, developed through an iterative participatory action research process, has proven to be effective in improving targeted relationally aggressive urban girls' social problem-solving knowledge and decreasing levels of relational aggression, with effects being maintained 1 year after treatment. In the current article, we examine the broader effects of the F2F program. Findings suggest that the indicated F2F program has broader effects such as increasing prosocial behaviors, decreasing relational and physical aggression, and improving teacher–student relationships among non-targeted boys. In addition, the program demonstrated some effects for non-targeted girls including an increase in prosocial behaviors and improved teacher–student relationships. Implications for examining the cost-effectiveness of indicated interventions such as F2F are discussed.